Comparison of municipalities considering environmental sustainability via neutrosophic DEMATEL based TOPSIS - KILIÇ, HÜSEYİN SELÇUK (ELSEVIER SCIENCE INC, 2021)
Considering the increasing risk of various events to the environment, environmental sustainability has taken much more attention both by the academics and practitioners than the other topics. Every organization has its own responsibilities. However, public institutions have a more important role, since they have direct effect on all the community considering environmental sustainability. At this point, the performance evaluation of the municipalities becomes important and enables an effective management by not only indicating the existing status of the municipalities but also revealing the gaps for improvement. Hence, regarding the importance of environmental sustainability and performance evaluation, this study firstly provides the environmental sustainability dimensions with related indicators and presents an integrated methodology based on Neutrosophic Decision Making Trial and Evaluation Laboratory (N-DEMATEL) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) for the performance comparison of municipalities. Different from the classical DEMATEL, NDEMATEL addresses the inherent ambiguity and indeterminacy of decision making process while revealing the importance of factors considering the interaction between them. Afterwards, TOPSIS is used to determine the rank of the municipalities. So as to show the applicability of the proposed methodology, an application is performed in the district municipalities of Istanbul Metropolitan Municipality.
Keywords: Environmental sustainability; Performance evaluation; Municipality; Neutrosophic DEMATEL; TOPSIS; MULTICRITERIA DECISION-MAKING; MEASURING URBAN SUSTAINABILITY; HYBRID APPROACH; INDICATORS; FRAMEWORK; SELECTION; AHP; BENCHMARKING; EFFICIENCY; COMMUNITY